A performance evaluation method for energy storage systems adapted to new power system interaction requirements - Zhang, Zeya; Ma, Guozhen; Song, Nan; Wang, Yunjia; Xia, Jing; Xu, Xiaobin; Shen, Nuoqing (Frontiers in Energy Research, 2024)
In recent years, China's new energy storage application on a large scale has shown a good development trend, a variety of energy storage technologies are widely used in renewable energy development, consumption, integrated intelligent energy systems, distribution grids, microgrids, and substantial progress has been made in the research and development of technology and equipment, construction of demonstration projects, exploration of business models, and construction of standard systems. As of the beginning of 2023, a unified statistical index system and evaluation method standard for new energy storage has not yet been formed domestically or even internationally. The paper takes the status quo of new power system construction of Hebei South Network as the research object, and carries out the research on new energy storage statistical index system and evaluation method. It constructs a new energy storage power station statistical index system centered on five primary indexes: energy efficiency index, reliability index, regulation index, economic index and environmental protection index, proposes AHP-coefficient of variation combination assignment method, and evaluates the development level of the new energy storage power station by adopting comprehensive evaluation model based on the object element topology method.The new energy storage statistical index system and evaluation method are designed to provide a scientific index system and evaluation method for comprehensively monitoring, assessing and measuring the comprehensive performance and effect of new energy storage power plants in the process of operation and development, and optimizing the operation strategy of new energy storage power plants as well as the development and promotion of energy storage technology.